Eosinophilic cystitis as a rare cause of post-renal acute kidney injury in children: a case report - Kawalec, Anna; Wikiera-Magott, Irena; Apoznański, Wojciech; Rasiewicz, Katarzyna; Krajewski, Wojciech; Hałoń, Agnieszka; Zwolińska, Danuta (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Eosinophilic cystitis (EC) is a rare inflammatory disease of unclear etiopathology and various clinical presentations. We present a case of a 10-year old boy who was referred to our center because of acute kidney injury. The imaging diagnostic showed hydronephrosis, irregular thickening and infiltration of the posterior bladder wall. During cystoscopy, no ureter orifices were identified. Based on histopathological examination of bladder biopsy specimens, EC in an acute phase was diagnosed. To our knowledge the presented case is the first where EC led to post-renal acute kidney injury requiring hemodialysis. In the article we describe the diagnostic difficulties, therapy, clinical outcomes, and patient’s follow-up.